TAHAPAN-TAHAPAN DALAM PROSES PENGEMBANGAN KOLEKSI (Studi Kasus Perpustakaan Universitas Gajah Putih Takengon, Kabupaten Aceh Tengah) (Jurnal Adabiya, 2021)
Collection development is a core activity that has the task of holding and expanding collections in terms of collections in a library. The purpose of developing a collection is to expand and obtain a up-to-date collection. The University of Gajah Putih Takengon  Aceh Tengah Library is a private university library that functions as an information institution to support the implementation of the Tri Dharma Perguruan Tinggi. In supporting the implementation of the Tri Dharma Perguruan Tinggi and fulfilling the information needs of its users, libraries need to develop collections and formulate collection development policies. This paper examines the stages of the collection development process at the Gajah Putih Takengon University Library  Aceh Tengah regency and the collection development policy. This research uses qualitative methods with a descriptive approach. Data collection obtained through observation, interviews and literature study. The results showed that the stages of the collection development process at the Gajah Putih Takengon University Library Aceh Tengah regency were carried out simply without using a written collection development policy. In addition, the minimum number of librarians and budget is a logical factor for libraries in carrying out collection development activities.